Sobre la transformación integral de hankel-schwartz de funciones generalizadas (1990)
In this paper we study the Hankel-Schwartz transformations on certain spaces of testing functions denoted by T(λ, μ). Moreover, we define the generalized Hankel-Schwartz transforms on the spaces T(λ, μ) (duals of T(λ, μ)  of distributions.